2019
DOI: 10.1002/cam4.2484
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of laterality in renal cell carcinoma: A population‐based study from the surveillance, epidemiology, and end results (SEER) database

Abstract: Background Various prognostic characteristics have been established in the renal cell carcinoma (RCC). However, the impact of tumor laterality is unknown. The objective of the current study was to explore the predictive and prognostic impact of tumor laterality of RCC after surgery. Methods This investigation was a population‐based retrospective cohort study of patients with RCC from the surveillance, epidemiology, and end results (SEER) database in the USA. All patients received surgical treatment between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
4
19
3
2
Order By: Relevance
“…We also observed that the survived female patients have a significantly higher expression level of RGS5 compared with other categories (figure 5). Moreover, some studies reported better clinical results such as low grade tumours and better survival in patients with right-sided RCC compared with the left-sided RCC [34,35], but our result shows no significant difference between the expression level of RGS5 in female versus male patients with primary tumours located in the right kidney. However, among patients with primary tumours in the left kidney, female patients have a significantly higher RGS5 expression level (figure 4).…”
Section: Discussioncontrasting
confidence: 77%
“…We also observed that the survived female patients have a significantly higher expression level of RGS5 compared with other categories (figure 5). Moreover, some studies reported better clinical results such as low grade tumours and better survival in patients with right-sided RCC compared with the left-sided RCC [34,35], but our result shows no significant difference between the expression level of RGS5 in female versus male patients with primary tumours located in the right kidney. However, among patients with primary tumours in the left kidney, female patients have a significantly higher RGS5 expression level (figure 4).…”
Section: Discussioncontrasting
confidence: 77%
“…As we have known, the left renal vein has more vascular collateral circulation, which brings together multiple veins of the lumbar region and may induce more metastasis. Therefore, the left tumors may develop more metastasis than those on the right side (39). This idea is also reflected in the report of Morri et al (40) Owing to the concern for laterality, surgeons usually remove left lesions as possible, which leads to more negative margins being observed in left-sided cases.…”
Section: Discussionmentioning
confidence: 95%
“…Further analysis indicated that surgery and chemotherapy were independent prognostic factors for elderly patients, which is in agreement with previous studies of other cancers [ 23 25 ]. Moreover, treatments, such as surgery or chemotherapy, have already been proven to be prognostic factors for renal cancer [ 6 , 7 , 11 , 28 ]. Regarding other clinical characteristics, such as the year of diagnosis and laterality, although there were significant differences between the elderly group and the two younger groups, there was no trend of change with age.…”
Section: Discussionmentioning
confidence: 99%